Oscillations in modulus in solutions of graphene oxide and reduced graphene oxide with grafted poly-N-isopropylamide1. Issue 7 (21st February 2015) - Hashmi, Saud; GhavamiNejad, Amin; Stadler, Florian J.; Wu, Dongmei
<x xml:space="preserve">Abstract</x> In a material consisting of graphene oxide or reduced graphene oxide and poly-N-isopropylamide (PNIPAM) in an aqueous solution, a new type of complex rheological behaviour is found, which is a new type of rheochaos.